Penerapan Metode Role Playing untuk Meningkatkan Hasil Belajar Statistika Siswa Sekolah Dasar - Putri Nurmasyita; Sirajuddin Sirajuddin; Sri Satriani (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
Application of the Role Playing Method to Improve Statistics Learning Outcomes of Elementary School Students. This study aims to find out the results of learning statistics on data presentation and calculating the average (mean) through the role playing method in learning mathematics. Classroom action research was carried out at Mangasa 1 Public Elementary School, Somba Opu District by taking 26 research subjects. This research was conducted in 2 cycles. Each cycle consists of planning, implementation, observation and reflection activities. Data was collected using a filled-in test with a total of 10 questions. Data on learning outcomes were analyzed using a quantitative descriptive analysis method, namely finding the average student score and learning completeness. Data were taken from two activities, namely cycle I and cycle II. Learning outcomes data obtained by students in cycle I, namely with an average value of 73.26 and learning completeness reached 46.15% and cycle II obtained an average value of 98.84 and learning completeness reached 100%. In this study it can be concluded that the application of the Role Playing method can improve the mathematics learning outcomes of fourth grade students.